Anthropology and New Testament theology - Maston, Jason, 1978-; Reynolds, Benjamin E., 1977- (London, UK : Bloomsbury, 2018)
This volume considers the New Testament in the light of anthropological study, in particular the current trend towards theological anthropology. The book begins with three essays that survey the context in which the New Testament was written, covering the Old Testament, early Jewish writings and the literature of the Greco -Roman world. Chapters then explore the anthropological ideas found in the texts of the New Testament and in the thought of it writers, notably that of Paul. The volume concludes with pieces from Brian S. Roser and Ephraim Radner who bring the whole exploration together by reflecting on the theological implications of the New Testament's anthropological ideas. Taken together, the chapters in this volume address the question that humans have been asking since at least the earliest days of recorded history: what does it mean to be human? The presence of this question in modern theology, and its current prevalence in popular culture, makes this volume both a timely and relevant interdisciplinary addition to the scholarly conversation around the New Testament.
Introduction / Jason Maston -- 'What is man?' : a wisdom anthropology / Jamie A. Grant -- On the anthropology of early Judaism : some observations / Matthias Henze -- Greco-Roman perspectives on anthropology : a survey of perspectives from 800 BCE to 200 CE / Timothy A. Brookins -- The familial anthropology of Matthew's gospel / Amy Richter -- The redemption of fallen humanity : theological anthropology and Mark's narrative world / Mark L. Strauss -- Turning anthropology right side up : seeing human life and existence Lukewise / Steve Walton -- The anthropology of John and the Johannine epistles : a relational anthropology / Benjamin E. Reynolds -- Enlivened slaves : Paul's christological anthropology / Jason Maston -- The eschatological son : christological anthropology in Hebrews / Amy L.B. Peeler -- Life as image bearers in the new creation : the anthropology of James / Mariam Kamell Kovalishyn -- 'Remember these things' : the role of memory in the theological anthropology of Peter and Jude / Karen H. Jobes -- Revelation's human characters and its anthropology / Ian Paul -- Son of God at the centre : anthropology in biblical-theological perspective / Brian S. Rosner -- The mystery of Christian anthropology / Ephraim Radner.
Includes bibliographical references (pages [263]-283) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Hermeneutics; Bible; Theological anthropology -- Christianity; Theology; Hermeneutics..; Theological anthropology -- Christianity..; Theology..; Criticism, interpretation, etc..